Effects of ethephon and low-temperature treatments on blood oranges (Citrus sinensis L. Osbeck): Anthocyanin accumulation and volatile profile changes during storage. (1st November 2022) - Chen, Jin; Liu, Feifei; Ismail, Balarabe B.; Wang, Wenjun; Xu, Enbo; Pan, Haibo; Ye, Xingqian; Liu, Donghong; Cheng, Huan
Graphical abstract: Highlights: Ethephon was applied to blood oranges for the first time to enhance anthocyanins. Ethephon combined with 8 °C treatment significantly increased the anthocyanin contents. Volatile profiles and volatile-active components of blood oranges were detected. Ethephon could alleviate the loss of active volatiles during cold storage. Abstract: Health-promoting anthocyanins in blood oranges can be enriched via appropriate postharvest storage conditions. Here, we explored the changes of anthocyanin accumulation and volatile profiles of Tarocco blood oranges ( Citrus sinensis L. Osbeck) treated by the low temperature alone and combined with ethephon (2 mg/mL) during 50 days of storage. The combination treatment of ethephon and low temperature (8 o C) significantly enhanced the levels of total anthocyanins (10.91 ± 0.25 mg/100 g) and individual cyanidin derivatives relative to low-temperature treatment alone. The increases of six cyanidin derivatives and three delphinidin derivatives identified by LC-MS/Q-TOF were consistent with the variation in total anthocyanins. Ethyl butanoate, ethyl 2-methylbutyrate, ethyl hexanoate, ethyl undecanoate, linalool, and d -limonene were identified as main contributors to overall aroma of fresh blood oranges. Volatile compositions and concentrations were decreased under different treatments of ethephon and temperatures, while ethephon could alleviate the loss of activity volatiles during cold storage.